The Use of Fillers in Proposal Seminar Presentation - Mohammad, Titien Fatmawaty; Napu, Novriyanto; Soleman, Adinda Rahmatika (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This research aimed to investigate the frequency and reasons for using fillers during proposal seminar presentations among students in the English Department. The study involved five students who took the proposal seminar exam on March 18, 2022. Using a mixed-method approach, data were collected and analyzed to identify the types and frequency of fillers used, as well as the underlying reasons for their use. The findings revealed that the frequency of unlexicalized fillers was higher (172 occurrences, average 74.78) compared to lexicalized fillers (31 occurrences, average 13.48). The main reasons for using fillers included nervousness, forgetting what to say, reflexive habits, and difficulty finding the right words. These results highlight the need for students to improve their speaking skills and practice more to minimize the use of fillers during presentations. Additionally, it is suggested that lecturers focus on reducing the use of fillers in speaking classes to enhance students' performance and confidence in public speaking. This research provides valuable insights for educators in developing more effective teaching strategies to improve students' oral communication skills.